Comparison of Discrete Artificial Potential Field Algorithm and Wave-Front Algorithm for Autonomous Ship Trajectory Planning - Agnieszka Lazarowska (IEEE Access, 2020)
The article presents a novel, efficient graph search algorithm for path planning. The algorithm was inspired by the potential field method and therefore it is called the Discrete Artificial Potential Field (DAPF) algorithm. Additional trajectory optimization algorithm is also applied as a path smoothing mechanism. The algorithm is intended for use in Intelligent Transportation Systems of autonomous ships. The algorithm was implemented in the MATLAB programming language and tested by extensive simulation experiments. Results show that the algorithm can generate a collision-free path in an environment with static and dynamic obstacles, achieving near-real run time. The algorithm was also compared with the state-of-the-art graph search algorithm - a wave-front algorithm. Obtained results demonstrate that DAPF achieves better results in terms of both solution quality and run time.